Mengelola Pembelajaran Kewarganegaraan Berbasis TIK di Perguruan Tinggi untuk Memperkuat Nasionalisme Mahasiswa - Sarbaini Sarbaini; Rabiatul Adawiah; Dian Agus Ruchliyadi; Wardiani Hiliadi (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2026)
This study examines how ICT-based civic learning is managed in higher education to foster students’ nationalism at Universitas Lambung Mangkurat (ULM), Faculty of Teacher Training and Education (FKIP), Banjarmasin. Civic learning, which includes Civic Education (Pancasila and Citizenship Education, PPKn), non-formal activities, and digital engagement, plays an important role in shaping students’ national values. However, its implementation remains insufficiently integrated and coordinated at the institutional level. Using a qualitative approach with grounded research methods, data were collected from students and lecturers across three departments: Mathematics Education, English Education, and Pancasila and Civic Education. The study analyzes how civic learning is implemented and managed across formal, non-formal, and ICT-based contexts. The findings show that the management of ICT-based civic learning remains fragmented. PPKn instruction tends to emphasize memorization and formal knowledge, limiting students’ critical awareness and emotional attachment to national values. Non-formal activities, particularly scouting, provide experiential learning that supports the development of discipline, leadership, collaboration, and patriotism. ICT and social media offer opportunities for interactive civic engagement; however, their use is not yet systematically managed, resulting in inconsistent learning practices and exposure to global cultural influences that may weaken national identity. In addition, institutional coordination, policy support, and evaluation mechanisms for ICT-based civic learning remain limited. The study highlights the need to strengthen the management of ICT-integrated civic learning through better alignment between curriculum, extracurricular activities, and digital engagement. A more structured and coordinated approach enables higher education institutions to enhance students’ cognitive understanding, affective attachment, and behavioral expression of nationalism in the digital era.